In situ dynamic observations of perovskite crystallisation and microstructure evolution intermediated from [PbI6]4− cage nanoparticles - Qin Hu (Nature Portfolio, 2017)
The photovoltaic performances of perovskite materials are strongly influenced by their crystallinity and film morphology. Here, the authors investigate the formation and morphology evolution mechanisms of lead halide perovskites and reveal that bulk polycrystals grow from intermediate [PbI6]4−cage nanoparticles.